Subjective Well-Being Pada Menantu Perempuan Yang Tinggal Dengan Ibu Mertua - Rini, Dyah Puspa; , Rini Lestari, S.Psi, M.Si (2017)
For most new couples living with their parents is an option that most people do. The conflict between the daughter-in-law and mother-in-law is a daily problem and almost everyone has experienced it. This is supported by several surveys and studies showing that the relationship between the daughter-in-law and mother-in-law had a disagreement more often compared to the relationship between the son-in-law and mother. This study used a qualitative method that aims to understand and describe the subjective well-being the daughter-in-law who lived with her mother-in-law. Subjects in this study live in Surakarta amounted to 4 people, taken using purposive sampling. The results obtained are less amenable daughter-in-law completely to live with mother-in-law. Daughter-in-law who lived with her mother-in-law has lack subjective well-being. Because, lived with her mother-in-law make the daughter-in-law could not be himself, oppressed, and more negative affective feel like disappointed, annoyed, angry, sad and depressed, thus making the daughter-in-law wants her own house. Factors that influence the subjective well-being daughter-in-law who lived with her mother is a good environmental mastery, affection, social relation and nature. Summary, daughter-in-law who lived with her mother is not able to feel the well-being of his life